Zoledronic acid inhibits the bone metastasis of breast cancer by repressing exosome-loaded DKK1 - Bin Bin Song; Mao Yi Xu; Xiao Fang Xu; Xia Li; Ming Chen (Bangladesh Pharmacological Society, 2022)
This study is designed to investigate the mechanism underlying zoledronic acid for the bone metastasis of breast cancer. Dickkopf 1 (DKK1) was both expressed in breast cancer cells and exosomes isolated from breast cancer cells. The expression of DKK1 was synchronously inhibited in breast cancer cells and exosomes with zoledronic acid or transfecting with cDNA3.1-DKK1. The proliferation and migration of MDA-MB-453 cells were greatly repressed and the differentiation and maturity of osteoclasts were dramatically repressed by exosomes derived from zoledronic acid-treated MDA-MB-453 cells. In the co-cultural system of RAW264.7 cells and MDA-MB-453 cells, the proliferation and migration of MDA-MB-453 cells were facilitated by exosomes derived from MDA-MB-453 cells. Lastly, the EMT progression and TGF-β signaling were significantly blocked by exosomes derived from zoledronic acid-treated MDA-MB-453 cells. Zoledronic acid suppressed the bone metastasis of breast cancer by inhibiting the exosomes loaded with DKK1.